Recruiting Immigrant and Refugee Arab American Mother–Father–Infant Triads Resettling in the United States: A Feasibility Study. Issue 2 (June 2020) - Khalil, Dalia; Giurgescu, Carmen; Misra, Dawn P.; Templin, Thomas; Javanbakht, Arash
Background: Recent Iraqi and Syrian immigrant families are exposed to stress, anxiety, and depressive symptoms due to civil war. Recruitment challenges specific to conducting research within this population include the lack of knowledge about research, stigma of mental illness, and mistrust. Purposes: Among immigrant Iraqi and Syrian families: (1) evaluate the approach to recruitment and retention; and (2) evaluate the acceptability of the study procedures. Methods: This feasibility study was conducted based on the work of Orsmond and Cohn. It is focused on the evaluation of recruitment capability and resulting sample characteristics and evaluation of acceptability and suitability of the study procedures. Mother–father–infant triads were recruited from a community center. Parents completed questionnaires about stress and depressive symptoms. Buccal swab samples were obtained from the triads to measure telomere length, and infant hair samples were obtained to measure cortisol level. Telomere length and hair cortisol were utilized as measures of chronic stress. Results: Ten mother–father–infant triads were enrolled out of 11 approached. Challenges faced this study included inability to reach families by telephone and the effect of cultural norms where the husband's permission was needed before proceeding, resulting in a slow pace of recruitment. The study strategy and procedures appeared to be feasible as all of the families who participated completed all study protocols. Conclusion: This study provides feasibility data to inform the launching of a larger study to examine the associations of family stress with infant stress and development. These findings from Iraqi and Syrian families may be generalizable to studies seeking to recruit these and other immigrant and refugee population families.